2020
DOI: 10.1016/j.bbagrm.2020.194489
|View full text |Cite
|
Sign up to set email alerts
|

The world of asRNAs in Gram-negative and Gram-positive bacteria

Abstract: Bacteria exhibit an amazing diversity of mechanisms controlling gene expression to both maintain essential functions and modulate accessory functions in response to environmental cues. Over the years, it has become clear that bacterial regulation of gene expression is still far from fully understood. This review focuses on antisense RNAs (asRNAs), a class of RNA regulators defined by their location in cis and their perfect complementarity with their targets, as opposed to small RNAs (sRNAs) which act in trans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 130 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…Transcriptomic studies have shown that bacteria synthesize an array of antisense regulatory RNAs [ 53 ]. These molecules vary greatly in their size, their location in respect to sense strand genes, and the mechanisms by which they impact gene expression levels [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomic studies have shown that bacteria synthesize an array of antisense regulatory RNAs [ 53 ]. These molecules vary greatly in their size, their location in respect to sense strand genes, and the mechanisms by which they impact gene expression levels [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic studies have shown that bacteria synthesize an array of antisense regulatory RNAs [ 53 ]. These molecules vary greatly in their size, their location in respect to sense strand genes, and the mechanisms by which they impact gene expression levels [ 53 ]. A variety of bacterial antisense RNAs have been characterized and shown to play a role in regulating motility, iron acquisition, and biofilm development [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In bacterial pathogens, several examples of asRNAs overlapping an RBS have been described, and they go beyond plasmid replication-related functions ( Thomason and Storz, 2010 ; Lejars and Hajnsdorf, 2020 ). This is the case in Pseudomonas , Salmonella , Shigella , Clostridioides difficile , L. monocytogenes , and S. aureus , although precise demonstrations of this mechanism of action are lacking, and it is often linked to transcript abundance variations, as recently reviewed ( Lejars and Hajnsdorf, 2020 ). This indicates that translation inhibition and mRNA decay are often concomitant, as we will see for RNAIII in the next section.…”
Section: Classification Of Base-pairing Acting Srnas According To Their Origins and Mechanisms Of Actionmentioning
confidence: 99%
“…The leaf extracts can inhibit infection and proliferation of influenza A, H7N9, encephalitis B, mumps viruses, HSV-II, Dengue virus II, and Cytomegalovirus, among others (Ma, 2014 ; Zhou et al, 2006 ); directly neutralize and degrade endotoxin in actinomycin D-sensitized mice (Shi and Zhang, 2006 ) and promote interleukin 2 (IL-2) secretion by spleen lymphocytes induced by concanavalin A to enhance immunity in normal mice (Hsuan et al, 2009 ; Liang et al, 2000 ). They also have anti-bacterial effects against Staphylococcus aureus and Escherichia coli (Lejars and Hajnsdorf, 1863 ) and promote bile excretion and relieve pain (Hong et al, 2010 ; Liu et al, 2009 ). The root extracts have similar activities, such as inhibiting the human H7N9 avian influenza virus by preventing the virus from invading the host cells; inhibiting HSV-1 by preventing its replication and proliferation in cells; inhibiting E. coli , Staphylococcus epidermidis , Pneumococcus , Haemophilus influenzae , and Streptococcus ; and decreasing the levels of tumor necrosis factor-α (TNF-α) and IL-6 in peritoneal macrophages of mice (Hu et al, 2003 ; Wang et al, 2012 ).…”
Section: Clinical Applications and Pharmacological Activities Of I Indigoticamentioning
confidence: 99%